The everyday lives of young children : culture, class, and child rearing in diverse societies - Tudge, Jonathan (Cambridge ; New York : Cambridge University Press, 2008)
"This book is based on lengthy observations of three-year-olds in the United States, Russia, Estonia, Finland, Korea, Kenya, and Brazil. The focus is on how and where children spend their time, and who they are with, at an age when they are learning what it means to be a part of their culture. The book provides unique insight into variations in young children's lives in different societies and from different social-class groups. This book also has a clear theoretical rationale and illustrates how the observational methods were based on the theory."--Jacket.
8. Everyday lives. Morning ; Andy, in Greensboro ; Naomi, in Greensboro ; Boris, in Obninsk ; Peeter, in Tartu ; Jukka, in Oulu ; Jonghee, in Suwon ; Fredah, in Kisumu ; Gabriela, in Porto Alegre ; Summary ; Afternoon ; Mike, in Greensboro ; Sandra, in Greensboro ; Kolya, in Obninsk ; Heino, in Tartu ; Jonas, in Oulu ; Mikyung, in Suwon ; Brendah, in Kisumu ; Mariana, in Porto Alegre ; Summary ; Early evening ; Cassandra, in Greensboro ; Kevin, in Greensboro ; Liuba, in Obninsk ; Epp, in Tartu ; Teija, in Oulu ; Juwon, in Suwon ; Brandon, in Kisumu ; Francisco, in Porto Alegre ; Summary ; Preparing for sleep ; Patty, in Greensboro ; Noel, in Greensboro ; Volodya, in Obninsk ; Eva, in Tartu ; Piia, in Oulu ; Dongki, in Suwon ; Derrick, in Kisumu ; Daniel, in Porto Alegre ; Summary ; Conclusion -- 9. The cultural ecology of young children. Culture and human development ; Illustrating a dialectical approach to culture and human development ; Cultural and social-class influences on development ; Individual influences on development ; The influence of time on and in development ; Conclusion.
Includes bibliographical references (pages 283-302) and index.
Keywords: Children -- Cross-cultural studies; Social interaction -- Cross-cultural studies; Children; Social interaction; Cross-cultural studies